Investigation of photochemical and photophysical properties of novel silicon(IV) phthalocyanines and their ?-oxo dimers - Gungor, Omer; Durmuş, Mahmut; Ahsen, Vefa (Tubitak Scientific & Technological Research Council Turkey, 2017)
The synthesis and characterization of novel tetraalkylthio (SC6H13 or SC12H25) substituted mu-oxo silicon(IV) phthalocyanines (3a and 3b) and their mu-oxo derivatives (4a and 4b) were described in this study. These silicon(IV) phthalocyanines were characterized using different spectroscopic techniques such as UV-Vis, H-1 NMR, FTIR, and mass and elemental analysis, as well. Furthermore, the photophysical (fluorescence quantum yields and lifetimes) and photochemical (singlet oxygen generation) properties of the newly synthesized silicon(IV) phthalocyanines (3a, 3b, 4a, and 4b) were investigated in dimethylformamide solution. The absorption and fluorescence excitation wavelengths of the studied silicon(IV) phthalocyanines were blue-shifted when they converted to their mu-oxo dimers. The fluorescence quantum yield and lifetime values decreased with the substitution of the tetraalkylthio groups on the phthalocyanine ring. The singlet oxygen generation of the studied silicon(IV) phthalocyanines increased with the formation of the mu-oxo bridge between two phthalocyanine rings.
Keywords: Phthalocyanine; silicon; photochemical; photophysical; singlet oxygen; fluorescence